DeepSeek-V3 Training Stability Optimizations for Scalable Code Completion - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: How does the training stability optimization in DeepSeek-V3 influence convergence speed and final accuracy on code completion tasks across different dataset scales. 12 claims were extracted from source literature; 10 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.6/10. This report is a machine-generated literature
Machine-generated literature synthesis.